Effect of dietary fiber (inulin) addition on phenolics and in vitro bioaccessibility of tomato sauce - Tomas, Merve; Beekwilder, Jules; Hall, Robert D.; Diez Simon, Carmen; Sagdic, Osman; Capanoglu, Esra (Elsevier BV, 2018)
The effect of the addition of inulin (5 and 10%) on the phenolic content and in vitro gastrointestinal digestion of tomato sauces has been investigated. Results have shown that the addition of inulin to tomato sauce significantly decreased the total phenolic content (57-68%), total flavonoid content (48-60%), and total antioxidant capacity (49-61%). Similarly, all assays of the sauce containing both 5% and 10% inulin, showed a slight decrease during in vitro gastrointestinal digestion of tomato sauces. Higher levels of inulin added to tomato sauce resulted in the greatest decrease in phenolic content, probably because of the interaction between inulin and phenolic compounds. To address the effects of inulin on the global metabolite profile of tomato sauce, an untargeted metabolomics approach was followed. Changes related to the presence of inulin suggest that inulin quenches a subset of unidentified compounds which are present in sauce but not in fruit, suggesting that inulin can contribute to the conservation of fruit properties in tomato sauce.
Keywords: Dietary Fiber; Flavonoids; Bioavailability; Food Handling; Inulin; In vitro gastrointestinal digestion; Biological Availability; Dietary fiber; Antioxidants; Tomato sauce; Solanum lycopersicum; Phenols; Fruit; Food matrix; Humans; Metabolomics; Antioxidant